Academic Primer Series: Five Key Papers about Study Designs in Medical Education - Michael Gottlieb; Teresa M. Chan; Jenna Fredette; Anne Messman; Daniel W. Robinson; Robert Cooney; Megan Boysen-Osborn; Jonathan Sherbino (Western Journal of Emergency Medicine, 2017)
Introduction: A proper understanding of study design is essential to creating successful studies. This is also important when reading or peer reviewing publications. In this article, we aimed to identify and summarize key papers that would be helpful for faculty members interested in learning more about study design in medical education research. Methods: The online discussions of the 2016–2017 Academic Life in Emergency Medicine Faculty Incubator program included a robust and vigorous discussion about education study design, which highlighted a number of papers on that topic. We augmented this list of papers with further suggestions by expert mentors. Via this process, we created a list of 29 papers in total on the topic of medical education study design. After gathering these papers, our authorship group engaged in a modified Delphi approach to build consensus on the papers that were most valuable for the understanding of proper study design in medical education. Results: We selected the top five most highly rated papers on the topic domain of study design as determined by our study group. We subsequently summarized these papers with respect to their relevance to junior faculty members and to faculty developers. Conclusion: This article summarizes five key papers addressing study design in medical education with discussions and applications for junior faculty members and faculty developers. These papers provide a basis upon which junior faculty members might build for developing and analyzing studies.